1991
DOI: 10.1111/j.1432-1033.1991.tb15712.x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual class I (Schiff base) fructose‐1,6‐bisphosphate aldolase from the halophilic archaebacterium Haloarcula vallismortis

Abstract: An electrophoretically homogeneous class I (Schiff base) alsolase has been isolated for the first time from the archaebacterial halophile Haloarcula (Halobacterium) vallismortis. The aldolase was characterized with respect to its molecular mass, amino acid composition, salt dependency, immunological cross-reactivity and kinetic properties. The subunit mass of aldolase is 27 kDa, which is much smaller than other class I aldolases. By the gel filtration method, the molecular mass of the halobacterial enzyme was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…vallismortis and Tco. kodakarensis (130,133). Despite the lack of significant overall sequence identity, the structural similarity of the two types of FBPA I enzymes suggests a common ancestry and, thus, homology (135,136).…”
Section: Fructose-16-bisphosphate Aldolase (Catabolic)mentioning
confidence: 99%
See 1 more Smart Citation
“…vallismortis and Tco. kodakarensis (130,133). Despite the lack of significant overall sequence identity, the structural similarity of the two types of FBPA I enzymes suggests a common ancestry and, thus, homology (135,136).…”
Section: Fructose-16-bisphosphate Aldolase (Catabolic)mentioning
confidence: 99%
“…furiosus, and Tco. kodakarensis (126,130,132,133). Two classes of FBPAs, which differ with respect to reaction mechanisms and distributions in the biosphere, have been identified (for literature, see reference 134).…”
Section: Fructose-16-bisphosphate Aldolase (Catabolic)mentioning
confidence: 99%
“…Although several enzymes of the proposed modified EM pathway in haloarchaea, ketohexokinase, 1-PFK, and class I and class II type FBA, have been purified (21,31,36,37), the genes encoding these enzymes have not been identified so far, and their functional involvement in fructose catabolism has not been demonstrated. Recently, the fructose-specific upregulation of a gene (HVO_1500) encoding putative 1-PFK has been reported for H. volcanii, and the role of a transcription regulator (GlpR) in fructose catabolism has been analyzed (39).…”
mentioning
confidence: 99%
“…Although Class I and Class II FBP aldolase activities have been demonstrated in Archaea (15)(16)(17)(18)(19)(20)(21), no genes encoding classical Class I or II enzymes have been identified in any of the sequenced archaeal genomes suggesting that Archaea possess novel types of aldolases that are either absent or not yet recognized as such in Bacteria and Eucarya. The latter is supported by initial data base searches of Galperin et al (22) who identified gene homologs of the unusual Class I FBP aldolase gene (dhnA) of E. coli in the sequenced archaeal genomes.…”
mentioning
confidence: 99%